Falls in a single brain rehabilitation center: a 3-year retrospective chart review - Yoo Jin Choo; Jun Sung Moon; Gun Woo Lee; Wook-Tae Park; Min Cheol Chang (Frontiers in Neurology)
ObjectiveFalls in brain rehabilitation centers can negatively impact patient recovery, increase injury risk, and adversely affect rehabilitation outcomes. This study aimed to analyze the incidence of falls and identify associated risk factors among patients with brain lesions in a tertiary hospital’s brain rehabilitation center from June 2021 to May 2024.MethodsA retrospective chart review was conducted to examine patient characteristics, fall-related risk factors, functional assessments, and circumstances surrounding falls.ResultsAmong 316 patients, 10 (3.2%) experienced falls, with a mean age of 61.3 ± 11.9 years. Most patients demonstrated walking and cognitive impairments. Seven falls (70%) occurred during attempts to get out of bed, with five of these incidents occurring at night. Falls were observed despite the presence of caregivers and bed rails. Additionally, all 10 patients were administered medications that may increase fall risk, such as somnifacients or tranquilizers. The occurrence of falls appeared to be associated with multiple factors, including physical limitations (e.g., impaired mobility, visual disturbances, and medication side effects), environmental conditions (e.g., inadequate lighting and medical staff shortages), and behavioral aspects (e.g., unassisted movement).ConclusionTo mitigate fall risk, a comprehensive approach that includes improved nighttime lighting, education on assistive device use and medication management, caregiver training, and personalized rehabilitation programs may be beneficial.